Tuning the structural, electrical and optical properties of tin oxide thin films via cobalt doping and annealing. (July 2016) - El Sayed, A.M.; Taha, S.; Shaban, Mohamed; Said, G.
Abstract: Pure and cobalt-doped SnO2 (Sn1− x Co x O2, 0 ≤ x ≤ 0.09) thin films were grown by dissolving SnCl2 ·2H2 O in ethanol and spin coating on glass substrates. The X-ray diffraction and Raman analysis show that the films are polycrystalline and correspond to the rutile phase with a preferred orientation along (110) direction. The grain size and crystallinity of the films that annealed at 450 °C for 1.0 h are enhanced after annealing at 500 °C for 2.0 h. According to atomic force microscopy (AFM), the films consist of grains influenced by doping and annealing temperature and time. I–V measurements reveal non-Ohmic contacts of the films with the electrodes. Transmittance spectra, optical band gap (Eg ), Urbach energy (EU ), refractive index, film thickness, and the optical constants of the films are dependent on the Co content and annealing conditions. The obtained results illustrate the possibility of controlling the film's physical properties for the optoelectronic devices and applications. Graphical abstract: Highlights: Homogeneous SnO2 films are prepared by spin coating without using any chelating agent. The effects of Co doping and annealing on the films' structure studied by XRD and AFM. There are a dependence of I-V curves and σdc of the films on Co content and annealing. The E g and E U values of the films can be tuned by Co content and annealing conditions. The optical constants of the films were determined based on Swanepoel's model.